2010
DOI: 10.1086/648568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ontogenetic Changes in Branchial Morphology on Gill Function inArapaima gigas

Abstract: Soon after hatching, the osteoglossid fish Arapaima gigas undergoes a rapid transition from a water breather to an obligate air breather. This is followed by a gradual disappearance of gill lamellae, which leaves smooth filaments with a reduced branchial diffusion capacity due to loss of surface area, and a fourfold increase in diffusion distance. This study evaluated the effects these changes have on gill function by examining two size classes of fish that differ in gill morphology. In comparison to smaller f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
57
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 37 publications
9
57
2
Order By: Relevance
“…Almost half of the MRCs are immature cells with low immunoreactivity against Na 1 /K 1 -ATPase (light MRCs) and are not in contact with the environment. This result was clearly evidenced by the lower MRC frequency at the epithelial surface compared to the total MRC frequency in the gill epithelium and agrees with the differences in the gill Na 1 /K 1 -ATPase activity in small and large fish reported by Gonzalez et al (2010). In A. gigas, the kidney most likely plays an important role in ion and pH regulation Gonzalez et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Almost half of the MRCs are immature cells with low immunoreactivity against Na 1 /K 1 -ATPase (light MRCs) and are not in contact with the environment. This result was clearly evidenced by the lower MRC frequency at the epithelial surface compared to the total MRC frequency in the gill epithelium and agrees with the differences in the gill Na 1 /K 1 -ATPase activity in small and large fish reported by Gonzalez et al (2010). In A. gigas, the kidney most likely plays an important role in ion and pH regulation Gonzalez et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the morphological changes in the gills of A. gigas may reduce the capacity of O 2 to diffuse through the lamella. Previous data showed that the percentage of O 2 uptake by the gills of fish weighing between 2,000 and 3,000 was only 23% (Stevens and Holeton, 1978); however, some physiological adjustments for compensating the gill morphological restrictions may occurs in fish smaller than 1,000 g, as Gonzalez et al (2010) reported higher O 2 uptake percentage in 724.2 g fish (30%) than in 67 g fish (24%).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations